Forensische Verfahren in den zeitgenössischen Künsten Forensic Architecture und andere Fallanalysen - Stuckey, Lisa (Undisziplinierte Bücher, 2022)
The research agency Forensic Architecture investigates war crimes and ecological and political crises, and brings them to both exhibition spaces and courtrooms by applying its "investigative aesthetics" (MACBA 2017). Using the figuration "Law on Trial," Lisa Stuckey determines why it is precisely aesthetic and poetic forensic procedures that are assigned the task of radically questioning social justice.